Experimental Analysis of Adhesive Joint Strength and Moisture Level of Pineapple Leaf Fiber (PALF) from Different Location within a Stem - Dessy Syapoetri; amin rejo; rizky tirta adhiguna; harsyamsi Wahab (Program Pascasarjana Universitas Sriwijaya, 2019)
The utilization of pineapple leaf fiber (PALF) as textile fiber material will have a very important meaning that is in terms of utilization of agro-waste. Pineapple leaf fiber (PALF) has different characteristics due to pineapple leaf’s position. Utilization of PALF from base of the plant stem is more appropriate to be used as textile fiber material. PALF categorized as staple fiber (short fiber) which needs to have a connecting process. The connecting process is usually carried out by dead knotted.The research objective was to know the effect of the location of pineapple leaves and various adhesive materials to characteristics of pineapple fibers. The research was conducted on September 2018 until March 2019 at Department of Agricultural Technology Sriwijaya University and Center for Textiles in Bandung, West Java Province. The research used Factorial Completely Randomized Design (RALF) with two treatment factors of the pineapple fibers location in the stem consisting of three levels namely the upper part (A1), the middle (A2) and the bottom (A3) and the type of adhesive consisting of two levels, polyvinyl alcohol (B1) and polyester resin (B2). This research consisted three parameters of moisture content (%), tensile strength / bundle (gf), and tensile strength (gf). The result of this research showed that the difference of location of fibers in pineapple leaves affect the moisture content (%), tensile strength / bundle (gf), and tensile strength (gf). The combination of interaction location of pineapple fibers on leaves and the type of adhesive significantly affected the moisture content (%) of MC and MR, tensile strength / bundle (gf) of Fmax and Emax. The best treatment was found on the treatment combination of lower fiber treatment and polyester adhesive (A3B2), namely MC 3.18%, MR value in A3B2 treatment of 3.28%. The best treatment of tensile strength / bundle is in the A3B2 treatment of 1779.8 gf for the value of F max and the E max value found in the treatment A3B2 which is 4.79%.